Pre-Roman Libyan Religion: Colonial Ethnography and the Problem of Religious “Survivals” - McCarty, Matthew M. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2021)
Since its inception, the study of Iron Age North African (“Libyan”) religion has been bound up with European ethnographic accounts of modern Berber practices and mentalities. Analyses are based around notions of “survival” and “permanence” observed in later (Roman, post-antique) material and retrojected as belonging to an earlier stage. This approach is itself drawn from 19th century anthropology, and remains current. To move the study of Iron Age cult forwards, we must pose new questions which recognise that religión is never an ahistorical mentality, but rather is entangled with dynamics of social power and lived experience.